PRAKTIK PENGGUNAAN QRIS DALAM PENGUMPULAN INFAK DAN SEDEKAH DI MASJID AR-RAUDHAH KECAMATAN BANTAN - Difa Rizkia; Sri Rahmany; Ahmad Shirotol; Ali Ambar (CV. KAMPUS AKADEMIK PUBLISING, 2023)
This type of research is field research. The research methods used were observation, interviews, documentation and literature studies conducted at the Ar-Raudhoh Mosque, Bantan District. The research subjects were the administrators and congregation of the Ar-Raudhoh Mosque, Bantan District, while the research object was the QRIS payment system used in electronic transactions for infaq and alms at the Ar-Raudhoh Mosque, Bantan District. Data can be analyzed qualitatively which produces descriptive data. The results of research on the practice of using QRIS in collecting donations and alms at the Ar-Raudhoh Mosque, Bantan District, 1) The practice of using QRIS in electronic transactions for donations and alms at the Ar-Raudhoh Mosque is in accordance with Bank Indonesia, namely that first the congregation must have the M-Application. Banking or E-Wallet such as BRIMO, BRKS mobile, OVO, DANA, Shopeepay and others. Open the application and select the QRIS menu, a scan camera will appear. After that, direct the scan to the QR code that has been provided, with that the camera will automatically scan the code and the name of the recipient will appear, namely the name of the Ar-Raudhoh Mosque and write the nominal amount of money that will be donated. Check all the information listed such as the recipient's name, namely the Ar-Raudhoh Mosque and the nominal amount, then complete the transaction, then the transaction will be immediately received in the Ar-Raudhoh Mosque account. 2) Review of the principles of sharia economic law regarding the use of QRIS for infaq and alms at the Ar-Raudhoh Mosque, Bantan District. Based on the MUI DSN Fatwa, namely to realize the benefit of humanity and all transactions in muamalah are basically legal until an argument is found that prohibits it.